Simultaneous optimization of the thermal conductivity and mechanical properties of epoxy resin composites through PES and AgNP functionalized BNs. (1st January 2023) - Luo, Jiamei; Yang, Xueqin; Xue, Yi; Yang, Chenxi; Yang, Zehao; Tusiime, Rogers; Liu, Yong; Zhang, Hui; Yu, Jianyong
Abstract: In this work, polyether sulfone (PES) and silver nanoparticles functionalized boron nitride nanoplates (AgBNs) were adopted to simultaneously improve the thermal conductivity and mechanical properties of the epoxy resin (EP) composites. The 0D silver nanoparticles (AgNP), successfully manufactured by the reduction reaction of DMF and AgNO3, were conductive to increase the interfacial contact of 2D boron nitride nanoplates (BNs), thus also improving the heat conduction paths of AgBNs. SEM and optical microscopy observations revealed that the 3D continuous thermal conduction paths of AgBNs were constructed based on PES/EP bi-continuous phase structures, and were perfected as the AgBNs contents increased. Consequently, the thermal conductivity of PES-EP/AgBNs achieved a maximum value of 0.54 W m −1 K −1 at 10 wt% AgBNs loading, which was much higher than that of both EP/AgBNs (0.45 W m −1 K −1 ) and EP/BNs (0.36 W m −1 K −1 ) at the same filler content. Meanwhile, the fracture mode of PES-EP/AgBNs changed gradually from brittle to ductile, and PES-EP/AgBNs further exhibited satisfactory tensile strength, flexural strength and fracture toughness, in comparison with EP/AgBNs due to the introduction of PES. This approach reconciles efficiently the conflict of thermal conductivity and mechanical properties of epoxy resin composites, presenting conceivable applications in high performance thermal conductivity devices. Graphical abstract: Image 1